Delayed Romantic Experience: Association of Romantic Relationship and Weight Change Patterns over 7 Years among Taiwanese Adolescents. Issue 8 (November 2022) - Yeh, Jih-Cheng; Chen, Duan-Rung
Stigmatization of overweight and obese individuals is common in interpersonal relationships. This study investigated longitudinal weight change patterns among Taiwanese adolescents and the relationship of weight change patterns with delayed romantic experience from late adolescence to young adulthood by using a representative panel survey. Individuals were divided into six weight change pattern categories according to changes in their body mass index. Two-stage stratified and clustered sampling was used to obtain a representative student sample, and 1, 834 junior high school students were followed up over 7 years. Persistent obesity and a change from an underweight to a normal weight status over 7 years were independently associated with delayed romantic experience in both sexes. Moreover, females but not males who changed from an underweight or normal weight status to an overweight or obese status had increased odds of delayed romantic experience. Persistent obesity should be addressed early in life because it plays a crucial role in delayed romantic experience.